2015
DOI: 10.1002/jrs.4762
|View full text |Cite
|
Sign up to set email alerts
|

Raman spectroscopic investigations of epitaxial BiFeO3 thin films on rare earth scandate substrates

Abstract: BiFeO 3 epitaxial thin films fabricated by pulsed laser deposition on different scandate substrates were investigated by means of Raman spectroscopy. We observed periodic changes in Raman position, full width at half maximum and intensity for some phonon modes as a function of the azimuthal angle ϕ. Further analysis revealed the possibility to assign the so far controversial discussed Raman modes at low wavenumbers (<250 cm À1 ) through rotational Raman measurements at different azimuthal angles, which show hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 36 publications
0
15
0
Order By: Relevance
“…). For the BiFeO 3 phase, the Raman active modes were tentatively assigned according to the theoretical calculations recently published by Talkengerg et al As it can be observed, the spectra of both powders show bands corresponding to both the Bi 25 FeO 39 and Bi 2 Fe 4 O 9 secondary phases, together with those belonging to the BiFeO 3 . It is worth to mention that the presence of the Bi 2 Fe 4 O 9 phase in the BFTO powder was neither detected by XRD nor by the TEM analysis, probably due to its low proportion.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…). For the BiFeO 3 phase, the Raman active modes were tentatively assigned according to the theoretical calculations recently published by Talkengerg et al As it can be observed, the spectra of both powders show bands corresponding to both the Bi 25 FeO 39 and Bi 2 Fe 4 O 9 secondary phases, together with those belonging to the BiFeO 3 . It is worth to mention that the presence of the Bi 2 Fe 4 O 9 phase in the BFTO powder was neither detected by XRD nor by the TEM analysis, probably due to its low proportion.…”
Section: Resultsmentioning
confidence: 99%
“…Definitely, this enhanced capacity for the detection of minor byproducts may help in avoiding misleading conclusions (and discrepancies) on the functional response of this multiferroic system. ) observed in the experimental spectra of the BFO and BFTO powders (assignation to the BiFeO 3 modes or to the Bi 2 Fe 4 O 9 mullitetype and the Bi 25 FeO 39 sillenite-type secondary phases as explained in the text) and the calculated Raman wavenumbers for the BiFeO 3 modes from literature [27] Mode BFO BFTO Raman shift Calculated [27]…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…performed Raman spectroscopic investigations of epitaxial BiFeO 3 thin films on rare earth scandate substrates. Their results were supported by symmetry‐based calculations including the analysis of Raman scattering geometry as well as the dielectric function of BiFeO 3 in the IR range …”
Section: Solid‐state Studiesmentioning
confidence: 99%